Immigration Discourse and the Prospects of Russian Language in Lithuania - Likhachiova, Alla (Slavistica Vilnensis, 2019)
In contrast to the ongoing emigration, immigration to Lithuania cannot be called intensive, and this topic as a whole remains on the periphery of public and academic attention. This article offers a description of the situation of immigration from the perspective of sociolinguistics. In particular, an analysis of the discourse of today’s Russian-speaking immigration to Lithuania reveals the linguistic attitudes of immigrants with a native Russian language or their own, their adaptation strategies, family language planning, and, ultimately, makes it possible to formulate general conclusions about the prospects of preserving / not preserving Russian-speaking community in the host country. The paper summarizes interview materials with immigrants from Russia and some post-Soviet countries posted on the Lithuanian Internet, as well as recorded during this study.